Amyloid deposition with a granulomatous reaction in a resection specimen: A clue for a pre‐existing Merkel cell carcinoma. (5th July 2022) - Rothrock, Aimi T.; Truong, Luan D.; Shehabeldin, Ahmed; Wong, Michael K. K.; Cho, Woo Cheal; Nagarajan, Priyadharsini; Vanderbeck, Kaitlin; Curry, Jonathan L.; Torres‐Cabala, Carlos A.; Prieto, Victor G.; Aung, Phyu P.
Abstract: Merkel cell carcinoma (MCC) is an aggressive, highly metastatic, cutaneous neuroendocrine malignancy with poor prognosis. Here, we describe a MCC excision specimen with a rare case of tumor‐associated amyloid deposition in the absence of residual tumor cells. A 72‐year‐old man presented with a lesion of 5–6 months' duration on his left elbow, clinically thought to be a ganglion cyst. The biopsy specimen revealed a Stage IIA MCC with classic histomorphologic and immunophenotypic findings, with tumor extending to the tissue edges. The patient underwent wide local excision with negative margins and a negative sentinel lymph node biopsy. Although the patient did not receive any presurgical chemotherapy, immunotherapy, or targeted therapy, the re‐excision specimen showed only amphophilic, feathery deposits that were salmon‐pink with Congo red stain and further confirmed as amyloid by electron microscopy; there were no residual carcinoma cells. Amyloid deposition in MCC has been described in rare case reports. Our case was extraordinary in that there was only amyloid deposition and an associated granulomatous reaction, without identifiable MCC cells. This case demonstrates that amyloid deposition may be evidence of a prior MCC at the site of a prior procedure and may warrant careful evaluation for residual MCC.